A Hematopoietic Stem Cell Transplant Recipient with Nephrotic Syndrome and Immune Complex Deposits in Tubular Basement Membrane: A Rare Case Report (Iranian Journal of Kidney Diseases, 2023)
Following allogenic hematopoietic stem cell transplantation (HSCT), graft-versus-host disease (GVHD) may develop which may affect several organs. Although the presence of nephrotic syndrome after HSCT is rare, sometimes it occurs in the setting of GVHD. The most common histological finding on kidney biopsy of patients with proteinuria owing to GVHD is membranous glomerulonephritis (MGN). However, reports of immune complex deposition in the tubular basement membrane (TBM) and glomerular basement membrane (GBM) are extremely rare. Herein we present a 65-year-old female with a history of HSCT at six years ago who was referred to Dr.Shariati Hospital in Tehran with nephrotic syndrome. Secondary serologic laboratory tests were all normal. The histopathologic study indicated diffuse GBM and TBM thickening, spike formation, infiltration of inflammatory mononuclear cells in tubulointerstitial area and acute tubular injury in light microscopy. Immunofluorescence staining showed immune complex deposits in GBM, mesangial cells, and TBM.  DOI: 10.52547/ijkd.7550